Fundamentals of a program for grief counseling and facing with post-Covid-19 losses - Jaqueline García Rodríguez; Silvia Colunga Santos; Soledad Yanedy García Peláez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2023)
Background: when face-to-face activities restarted, the universities welcomed students who experienced losses related to Covid-19, caused or not by death, a situation that deserves to be addressed. Objective: to base, from the conceptual and methodological, a program aimed at teachers for grief counseling and facing with losses. Methods: a theoretical-reflexive analysis was carried out based on the systematization of publications in Spanish and English in the last three years. The terms: grief, university, coronavirus infections and counseling were introduced as descriptors. A screening of the eligible articles of the 76 found was carried out. A program for grief counseling and coping with post-Covid-19 losses was founded and prepared. Results: the program consists of three phases with general and specific indications, which can be modified by individualizing them. Evaluation instruments and intervention techniques are proposed. Conclusions: the program constitutes an adequate guidance instrument for teachers to help their students deal with grief.